2016
DOI: 10.1016/j.biortech.2015.11.018
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of product yields and inorganic content in process streams following thermal hydrolysis and hydrothermal processing of microalgae, manure and digestate

Abstract: ReuseUnless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or other rights-holder may allow further reproduction and re-use of this version -refer to the White Rose Research Online record for this item. Where records identify the publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
118
3
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(161 citation statements)
references
References 40 publications
24
118
3
5
Order By: Relevance
“…All pre-specified compounds were present in the organic yields with only 10 compounds reporting concentrations below 0.01 wt.%. It is worth to mention that nitrogen partitioned almost completely into inorganic form (simulated as ammonia), while sulphur remained attached in hetero form (simulated as 4-Isopropylthiophenol), similar to reports in [53]. Figure 6.…”
Section: Liquefaction Reactor Systemsupporting
confidence: 80%
“…All pre-specified compounds were present in the organic yields with only 10 compounds reporting concentrations below 0.01 wt.%. It is worth to mention that nitrogen partitioned almost completely into inorganic form (simulated as ammonia), while sulphur remained attached in hetero form (simulated as 4-Isopropylthiophenol), similar to reports in [53]. Figure 6.…”
Section: Liquefaction Reactor Systemsupporting
confidence: 80%
“…It is worth noting that the organic structure, solid-to-water ratio, residence time, pressure, catalysis and process units' mechanical configurations also influence the specific yields of each product as has been reported [4][5][6]9,11,[13][14][15][16]. However, such information available in literature is diverse and fragmented, and temperature levels remain the governing processing parameter that identify the product phase distribution.…”
Section: Introductionmentioning
confidence: 97%
“…From a system design perspective, hydrothermal treatment attempts to exploit the properties near-to the critical point of the algal water substrate for extraction and recycling of nitrogen and phosphorus nutrients, necessary for cultivation. Ekpo et al [13] showed that up to 90% of nitrogen was recovered in the aqueous phase at 350 • C and more than 97% at 500 • C, with only less than 10% of nitrogen detected in hetero form. Elliot et al [15] claimed that 50% of the nitrogen demand for cultivation purposes could be recovered by the aqueous recycling.…”
Section: Algal Biomass Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…However, these traditional uses have to be changed due to land limitations and the strict regulations [5]. The number of studies about the use of LSM as biomass to produce energy or other added-value products by anaerobic digestion of thermochemical processes has increased in recent years [6][7][8][9]. There are many different technologies which have been applied for biomass utilization.…”
Section: Introductionmentioning
confidence: 99%